Shaping Ability of Superelastic and Controlled Memory Nickel-Titanium File Systems: An In Vitro Study - Raidan A. Ba-Hattab; Dieter Pahncke (Hindawi Limited, 2018)
Improvements in the thermomechanical processing procedures of NiTi wires have led to the development of new NiTi instruments that compose mainly of martensite crystals, making the wire stable at clinical condition. This study aimed at comparing the shaping ability of two rotary nickel-titanium systems manufactured from different NiTi wires. Twenty simulated root canals each with a curvature of 35° in resin blocks were divided into two groups of 10 canals each. Canals in the first group were prepared with superelastic F360 instruments (Gebr. Brasseler, Germany) while canals in the second group were prepared using controlled memory HyFlex®CM™ instruments (Coltène Whaledent, Switzerland). Images were taken before canal preparation and after the use of each instrument. The assessment of the canal shapes was accomplished with a computer image analysis program. Data were statistically analyzed using SPSS program. Within the limitation of this in vitro study, HyFlex®CM™ instruments remained better centered in the apical third of the canals. In most canal segments, no significant differences were observed between either system in the amount of material removed. Both systems were comparable to each other in regards to their ability to enlarge root canal in the same way without procedural errors.